Pengelolaan Pembelajaran Pendidikan Agama Islam (PAI) Berbasis Ekologis di Sekolah Dasar (SD) Plus Al-Qodiri Jember - Azis, M. Abdul; Rizal, Syaiful (Sekolah Tinggi Agama Islam Taruna Surabaya, 2024)
This research aims to describe the problems that occur to students in educational institutions and efforts to overcome them. The problems of students include the increasingly weakening character or morals of students inside and outside the madrasah, the lack of application of Islamic values by students to their environment, and the lack of contribution of students in broadcasting the Islamic religion in society. The efforts that can be made to overcome this problem are the application of ecologically based educational methods in learning, especially in Islamic religious learning (PAI). PAI learning has a strategic role in implementing environmental awareness values because it must be provided at all levels of education. This research aims to formulate goals and steps in realizing environmental awareness through ecologically based PAI learning management. That is, in conducting research we carry out a descriptive qualitative research method with an intrinsic case study type of research. The results of this research ensure that students can implement Islamic values in protecting the environment by means of Ecologically Based Islamic Education Learning Management. From this description, it is clear that Ecologically Based PAI Learning Management can be a locomotive in increasing students' enthusiasm for learning to carry out activities outside the classroom and inside the classroom.